Case report: Teat stenosis in a suckler cow - Schären-Bannert, Melanie; Starke, Alexander; Snedec, Teja; Vogel, Laura; Wagner, Romy; Kühn, Tilman; Bittner-Schwerda, Lilli (Frontiers in Veterinary Science, 2023)
Bovine veterinarians are regularly confronted with teat lesions in cows. The number of studies on the diagnosis and treatment of teat lesions as well as the exchange of practical experience among clinicians are extensive in dairy cows compared with suckler cows. The aim of this case report was to describe the successful treatment of teat stenosis in a suckler cow and discuss possible challenges. A four-year-old Simmental cow, in her third lactation and four days in milk, was referred to our clinic along with her calf because of teat stenosis in the front left quarter. The owner had repeatedly used a rigid teat cannula in an attempt to relieve the stenosis during the previous lactation. However, the cow had refused to allow the current calf to suckle the affected teat and resisted attempts by the owner to cannulate the teat. The results of clinical examination, ultrasonography, and milk sampling showed stenosis of the proximal, middle, and distal parts of the front left teat cistern, accompanied by thelitis and cisternitis and mild chronic clinical mastitis. Based on published recommendations, treatment of the thelitis, cisternitis, and mastitis was initiated before resolution of the stenosis surgically. The first week of treatment included the administration of an intramammary product containing cefapirin and prednisolone, a systemic non-steroidal anti-inflammatory drug, a wax teat-boogie, and bandaging of the teat. Thereafter, the treatment was reduced to insertion of a wax-teat boogie and bandaging. Conservative treatment resulted in resolution of the mastitis, cisternitis, and stenosis in the proximal and middle parts of the teat, which had most likely been caused by repeated cannulation of the teat by the owner. Lateral theloscopy was then used to remove the distal stenosis, which was the primary lesion. Healing of the surgical wound and resolution of the swelling occurred several days postoperatively, and the calf's first attempt to suckle the teat was successful. The cow and calf were discharged from the clinic two weeks after surgery. A follow-up visit 4.5 months after surgery revealed that the calf was still nursing the teat and the operated quarter was producing a normal amount of milk.